Towards a better understanding of the HTL process of lignin-rich feedstock - Benedetta Ciuffi (Nature Portfolio, 2021)
Abstract The hydrothermal liquefaction reactions (HTL) in subcritical conditions of a lignin residue has been studied on a lab scale. The starting material was a lignin rich residue co-produced by an industrial plant situated in Northern Italy producing lignocellulosic bioethanol. The reactions were carried out in batch mode using stainless steel autoclaves. The experiments were under the following operating conditions: two different temperatures (300–350 °C), the presence of basis catalysts (NaOH, and NH4OH) in different concentrations and the presence/absence of capping agent 2,6-bis-(1,1-dimethylethyl)-4-methylphenol (BHT). Lignin residue and reaction products were characterized by analytical and spectroscopic techniques such as CHN-S, TGA, GC–MS, EPR, and 1H-NMR with (2,2,6,6-Tetramethylpiperidin-1-yl)oxyl (T.E.M.P.O.). The addition of BHT did not significantly affect the yield of char which is formed by radical way. Spectroscopic analysis indicated that the level of radicals during the reaction was negligible. Therefore, the results obtained experimentally suggest that the reaction takes place via an ionic route while radical species would play a minor role.